DYNAMIC DOUBLE-HOIST SCHEDULING IN SURFACE TREATMENT AREA USING HEURISTIC METHODS - Windia Habiba, Rahadini
Surface treatment plays a crucial role in enhancing metal quality and function by using chemical processes. In the automation process, optimal scheduling of surface treatment is important to optimize production efficiency and meet customer requirements. Taking case of one of Indonesian aircraft company, surface treatment with dynamic job characteristics involves double hoist to lifts crane of metals into multiple chemical tanks while considering operational constraints: minimum and maximum processing time, consecutive process sequence, hoist moving time while empty and loaded, no-wait scheduling, and collision-free between the two hoists. Such problem is called as Dynamic Double Hoist Scheduling Problem (DDHSP) and categorized as NP-hard. The objective of the study is to minimize the makespan required to complete all jobs. To address the problem, a combine of optimal computational scheduling using CPLEX followed by heuristic algorithm scheduling is introduced. The proposed algorithm is then evaluated using a set of benchmark and real surface treatment data from the aircraft company and compared with existing methods. Testing of the algorithm is then applied to hypothetic data. The results demonstrate that the combination of optional and heuristic algorithm exhibits smaller makespan in the schedule.